Maxillary sinus textiloma: a case report - Pons Yoann; Schouman Thomas (Journal of Medical Case Reports, 2010)
Abstract Introduction Textilomas have been reported in many locations. We report the first case of textiloma located in the maxillary sinus that mimicked a sinus cyst recurrence on computed tomography images. Case presentation A 60-year-old Caucasian man was referred for persistent infection of the right maxillary sinus. A maxillary sinus benign cyst had been removed three months before. Computed tomography showed a sinus opacity evoking a cyst recurrence. A new operation was planned to remove the cyst by a Caldwell-Luc approach. After excision of very thick fibrous tissue, a compress was discovered in the maxillary sinus. The patient did not present with any sinus infection after the operation. Conclusion The surgeon should always take into account the possibility of textilomas in a patient with a history of sinus surgery.